2008
DOI: 10.1007/s11706-008-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and antibacterial activity of chitosan microshperes in a solid dispersing system

Abstract: In this study, we investigated the interface contacting inhibition behaviors of chitosan against bacterial in the dispersing state. For that purpose, chitosan microspheres (CMs) in the dispersing state was prepared by the emulsification cross-linking method. The CMs had smooth surface and spherical shape with the diameter of about 124 mm. They were stable after sterilization at 121uC and 150 kPa for 20 min. The CMs had similar antibacterial activity to that of chitosan in the solution form. Their antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 25 publications
1
36
0
4
Order By: Relevance
“…Helander et al [72] reported that chitosan displayed antibacterial activity not only in an acid environment, although showed a stronger inhibitory effect at lower pHs with the inhibitory activity weakening with increasing pH. Kong et al [73] and Yang et al [74] observed that the antibacterial activity of the N-alkylated chitosan derivatives against E. coli increased as the pH rose from 5.0 reaching a maximum around pH 7.0-7.5. Also, the investigation of the antibacterial property of chitosan microspheres (CM) in a solid dispersing system showed that under neutral conditions, of the three tested CM samples with DA of 2.5, 16.5, 37.4% respectively, the highest inhibitory effect was observed for the CM sample with DA of 37.4% [73].…”
Section: Influence Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Helander et al [72] reported that chitosan displayed antibacterial activity not only in an acid environment, although showed a stronger inhibitory effect at lower pHs with the inhibitory activity weakening with increasing pH. Kong et al [73] and Yang et al [74] observed that the antibacterial activity of the N-alkylated chitosan derivatives against E. coli increased as the pH rose from 5.0 reaching a maximum around pH 7.0-7.5. Also, the investigation of the antibacterial property of chitosan microspheres (CM) in a solid dispersing system showed that under neutral conditions, of the three tested CM samples with DA of 2.5, 16.5, 37.4% respectively, the highest inhibitory effect was observed for the CM sample with DA of 37.4% [73].…”
Section: Influence Of Phmentioning
confidence: 99%
“…Kong et al [73] and Yang et al [74] observed that the antibacterial activity of the N-alkylated chitosan derivatives against E. coli increased as the pH rose from 5.0 reaching a maximum around pH 7.0-7.5. Also, the investigation of the antibacterial property of chitosan microspheres (CM) in a solid dispersing system showed that under neutral conditions, of the three tested CM samples with DA of 2.5, 16.5, 37.4% respectively, the highest inhibitory effect was observed for the CM sample with DA of 37.4% [73]. To date, there has been no positive information about the antimicrobial activity of chitosan under alkaline conditions.…”
Section: Influence Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Various sustained release drug carriers have been made from chitosan such as films [1][2], microspheres [3][4], nanoparticles [5][6], and gels [7][8]. Chitosan microspheres have been widely investigated for use as controlled release delivery systems for proteins [9], hormones [10], antibiotics [11], vitamin [12], and cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has caused a wide concern due to its unique biologic activity, such as immune enhancing effect [1], antitumor activity [2,3] and antimicrobial activity [4][5][6][7][8]. Previous research showed that chitosan possesses the characteristics favorable for promoting rapid dermal regeneration and accelerating wound healing [9,10] which were closely related to the collagen secretion and keloid forming.…”
Section: Introductionmentioning
confidence: 99%